2021
DOI: 10.3390/cancers13092106
|View full text |Cite
|
Sign up to set email alerts
|

CHEK2 Pathogenic Variants in Greek Breast Cancer Patients: Evidence for Strong Associations with Estrogen Receptor Positivity, Overuse of Risk-Reducing Procedures and Population Founder Effects

Abstract: CHEK2 germline pathogenic variants predispose to breast cancer and possibly to other malignancies, with their spectrum and frequency being variable among populations. Τhe majority of CHEK2-associated breast tumors are hormone receptor positive; however, relevant clinical outcomes are not well defined. Herein, we illustrate the histopathological characteristics and clinical outcomes of 52 Greek breast cancer patients who are CHEK2 carriers. Genetic analysis was performed by Sanger/massively parallel sequencing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The second variant in CHEK2, c.592+3A>T, was identified in one family with both breast and prostate cancer cases and segregation analysis has confirmed the cosegregation of the variant with the disease. This variant was predicted to lead to exon skipping and a recent RNA analysis in the study of Apostolou et al (2021) has confirmed that it leads to exon 3 skipping. In this same study, it was shown that c.592+3A>T is recurrent and founder mutation in the Greek population rising approximately 35 generations ago (Apostolou et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The second variant in CHEK2, c.592+3A>T, was identified in one family with both breast and prostate cancer cases and segregation analysis has confirmed the cosegregation of the variant with the disease. This variant was predicted to lead to exon skipping and a recent RNA analysis in the study of Apostolou et al (2021) has confirmed that it leads to exon 3 skipping. In this same study, it was shown that c.592+3A>T is recurrent and founder mutation in the Greek population rising approximately 35 generations ago (Apostolou et al, 2021).…”
Section: Discussionmentioning
confidence: 94%
“…This variant was predicted to lead to exon skipping and a recent RNA analysis in the study of Apostolou et al (2021) has confirmed that it leads to exon 3 skipping. In this same study, it was shown that c.592+3A>T is recurrent and founder mutation in the Greek population rising approximately 35 generations ago (Apostolou et al, 2021). These findings along with our results support the pathogenic effect of this variant and highlight the need for variant reclassification for better risk assessment and patients' management.…”
Section: Discussionmentioning
confidence: 94%
“…This discrepancy may be due to the fact that the CHEK2 c. 1100delC allele is rarely identified in breast cancer patients of Greek descent [ 47 ]. Pathogenic variants in CHEK2 are associated with an increased risk of estrogen receptor-positive breast cancer, although the risk decreases significantly with age, making these carriers more likely to develop the disease prior to menopause [ 48 , 49 ]. Notably, the I157T low-risk allele that was identified in two of our patients is associated with moderate risk and a more favorable prognosis [ 50 ].…”
Section: Discussionmentioning
confidence: 99%